Pengaruh Flash Sale, Interaktivitas Host, Dan Fomo Terhadap Impulse Buying Gen Z Pada Tiktok Live Shopping Produk Kecantikan GLAD2GLOW - Fadhilah Ma’rifatul Laily; Achmad Agus Priyono; Rahmawati Rahmawati (UNIVERSITAS ISLAM MALANG, 2026)
Abstract The development of social media, particularly the TikTok Live Shopping feature, has driven changes in Generation Z’s shopping behavior, especially in the purchase of beauty products. This study aims to analyze the effect of flash sales, host interactivity, and Fear of Missing Out (FOMO) on Generation Z’s Impulse Buying behavior on TikTok Live Shopping for Glad2Glow beauty products. This research employs a quantitative method with an explanatory approach, involving 85 respondents selected using a purposive sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS. The results show that flash sales, host interactivity, and FOMO simultaneously have a positive and significant effect on Impulse Buying behavior. Partially, flash sales and FOMO have a positive and significant effect, while host interactivity does not show a significant effect on Impulse Buying. These findings indicate that time-limited promotional strategies and psychological encouragement through FOMO play an important role in stimulating Generation Z’s Impulse Buying behavior on the TikTok Live Shopping platform. This study is expected to serve as a consideration for companies, particularly the Glad2Glow brand, in designing effective marketing strategies through TikTok Live Shopping. Keywords: Flash sale, Host Interactivity, Fear of Missing Out (FOMO), Impulse Buying, TikTok Live Shopping